Inquest verdicts: Youth suicides lost - Gosney, H; Hawton, K (2007)
Aims and method: To investigate how much reliance on suicide verdicts underestimates probable suicides. All unnatural deaths of those 8-18 years of age in West Yorkshire during a 6-year period were identified from the death register. Deaths which had verdicts other than killed him- or herself and were not obviously accidental were reviewed by a panel of three consultant child and adolescent psychiatrists to determine whether they were probable suicides. Results: Of 40 deaths reviewed by the panel, 13 were identified as probable suicides, of which 6 had an open verdict, 6 were death by self-hanging classified as misadventure and 1 was an overdose with a verdict of accidental death. These 13 deaths and the 7 with a coroner's verdict of suicide gave a total of 20 probable suicides. Clinical implications: Suicide statistics and targets need to take into account the fact that by current methods a significant proportion of suicides by adolescents will not be included in official figures. This underestimation would have been 65% if only suicides were identified and 35% when open verdicts were combined with suicides. Underestimating the youth suicide rate has consequences for the priority and resources allocated to preventing these deaths, and suicide deaths that are not recognised as such will not be included in relevant research and audit.